Updates on Actualizaciones en Sida e Infectología and the commitment to continue growing (Actualizaciones en Sida e Infectología, 2023)
30 years ago, Fundación Huésped began publishing its magazine Actualizaciones en SIDA (Updates on AIDS) with the aim of disseminating the different medical and social aspects related to the challenging problem of HIV/ AIDS. Twenty years later, in 2013, considering the prestige achieved by Actualizaciones en SIDA and the need for growth and expansion of its scientific dissemination channel, the Argentine Society of Infectious Diseases (SADI) joined as co-publishing institution. From that moment on, the contents of the journal were extended to all aspects related to infectious diseases beyond HIV/AIDS, so it was decided to change its name to Actualizaciones en Sida e Infectología (Updates on AIDS and Infectious Diseases) (ASEI). Many colleagues have contributed to make ASEI the main scientific journal in the field of infectious diseases in Argentina, and one of the most important in the Spanish-speaking world. But we want to go further! Those of us who are part of ASEI want to fulfill the dream of having a journal on infectious diseases indexed at the highest level. And we are working hard towards this goal.ASEI is currently included in the following databases:LILACS (Latin American and Caribbean Health Sciences Literature), http://lilacs.bvsalud.org/es/, This is one of the Open Access scientific literature databases of the Virtual Health Library Network of BIREME, the Latin American and Caribbean Center for Health Sciences Information of the Pan American Health Organization (PAHO) and the World Health Organization (WHO). Twenty-six countries in the region participate in LILACS and there are more than 603,000 bibliographic records of articles in Spanish, Portuguese and English published in full text in nearly 900 health sciences journals.  BINACIS - National Health Sciences Bibliography. It gathers the material of the cooperating centers of  the National Network of Health Sciences Information (RENICS). Since February 2018, BINACIS has been part of the BIREME Regional Index, which contains more than 144 thousand records. Latindex – Regional Online Information System for Scientific Journals of Latin America, the Caribbean, Spain and Portugal (Mexico). Latindex is an information system on scientific research, technical-professional and scientific and cultural dissemination journals published in Latin America, the Caribbean, Spain and Portugal. ASEI is currently part of the Latindex Directory, which provides bibliographic and contact information for all registered journals, both print and electronic. In addition, we will soon be applying for our journal to be included in the publications catalog of this scientific information database, for which we have been carrying out a process of modifications in the editorial policy in accordance with the requirements established by Latindex.Admission to the latter catalog will enable ASEI to submit its application to join the Basic Nucleus of Argentine Scientific Journals, a project of the National Council of Scientific and Technical Research of Argentina (Conicet) that establishes a set of national scientific and technological publications in different fields of knowledge that are subjected to an exhaustive evaluation with unique criteria defined by quality and importance. Currently, this database is made up of 359 journals, of which 50 are in the biological and health sciences.All these steps are necessary to try to gain access to the most relevant international scientific databases, such as MEDLINE, in order to further increase the dissemination and impact of our journal.As part of this restructuring process, ASEI has undertaken a renewal of the publishing advisors team, with the integration of a smaller Advisory Board with more active participation and editorial responsibility, and with members who will initially be renewed every two years.For this reason, we would like to thank so many professionals who have been with us for years as members of our Scientific and Advisory Committees, which have undoubtedly given prestige to the journal.Of course, all these changes are combined with the permanent invitation to our readers to continue contributing to these goals by submitting articles to be evaluated for publication in the journal. In this way, we will be able to fulfill the dream of having an Argentine journal of infectious diseases indexed in the main databases. We know it is possible, we just have to work for it!
Keywords: index; journal on infectious diseases